Adolescents' appearance-related behaviour and product use: the impact of sociocultural attitude towards appearance, gender, and body mass index on consumption. Issue 1 (2nd January 2018) - Yoo, Jeong-Ju; Yurchisin, Jennifer
ABSTRACT: The purpose of this study was to examine the associations among sociocultural attitude towards appearance (SATA), gender, body mass index (BMI), and adolescents' appearance-related behaviours and appearance-enhancing product use (e.g. hair dye, diet pills). A survey was conducted with a total of 292 adolescent boys ( n  = 128) and girls ( n  = 164). The results revealed that SATA, gender, and BMI all positively influence adolescents' appearance-related behaviours and product use. A major concern surrounded adolescents who highly valued SATA, as they were likely to engage in behaviours and use products that were designed to increase their attractiveness. Many of these products (e.g. steroids) and behaviours (e.g. sunbathing) were associated with dangerous consequences that adolescents may not fully comprehend.